2006
DOI: 10.1039/b516778g
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and reuse of ionic liquids and palladium catalyst for Suzuki reactions using organic solvent nanofiltration

Abstract: The separation, post-reaction, of ionic liquids and catalysts from reaction products is an unresolved challenge in the application of ionic liquids to organometallic catalysis. This paper addresses this challenge using organic solvent nanofiltration technology. Suzuki reactions were carried out in a homogeneous solution, comprising 50 : 50 wt% ethyl acetate and ionic liquid. The post reaction mixture was diluted further with ethyl acetate and then separated by nanofiltration into a permeate fraction and a reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…OSN is a technique for economic and efficient separation of molecules in the range of 200-1,000 g.mol -1 which are dissolved in organic solvents. It has been successfully applied in a variety of chemical processes such as catalyst recovery, solvent recycling, chiral separations and ionic liquid separation [3][4][5] . The most widely studied and commercialized OSN membranes are asymmetric polymeric membranes prepared by the phase inversion technique.…”
Section: Introductionmentioning
confidence: 99%
“…OSN is a technique for economic and efficient separation of molecules in the range of 200-1,000 g.mol -1 which are dissolved in organic solvents. It has been successfully applied in a variety of chemical processes such as catalyst recovery, solvent recycling, chiral separations and ionic liquid separation [3][4][5] . The most widely studied and commercialized OSN membranes are asymmetric polymeric membranes prepared by the phase inversion technique.…”
Section: Introductionmentioning
confidence: 99%
“…The purity of the recovered AmimCl was above 99%, confirmed by 1H NMR spectroscopy [Cao et al, 2007]. However, for the future industrial applications on a large scale, other methods suggested for removal of water may prove to be more practical [Wong et al, 2006;Swatloski et al, 2003]. These alternative methods include nanofiltration, reverse osmosis, pervaporation, and salting out of the IL.…”
Section: Ionic Liquids Recycling For Reuse 251mentioning
confidence: 99%
“…However, while solvent extraction is suitable for separation of apolar products, its use in separation of polar products is more problematic. For the latter case, a moderately polar extracting organic solvent is required, but since ILs tend to have significant partition coefficients into polar solvents, or are completely miscible with them, this can result in loss of IL to the product stream [Wong et al, 2006]. Fig.…”
Section: Ionic Liquids Recycling For Reuse 251mentioning
confidence: 99%
See 1 more Smart Citation
“…53 Organic solvent nanofiltration have been used to separate the product from both catalyst and ILs in some cases. 120 All the ILs screened showed positive effects on the catalytic stability, significantly reducing the formation of palladium black and providing high reaction yields over consecutive recycles.…”
Section: Suzuki Couplingmentioning
confidence: 99%